Vascular Closure Devices after Endovascular Procedures in Swine: A Reliable Method? - P. Isfort; T. Tanaka; T. Penzkofer; P. Bruners; R. Tolba; C. K. Kuhl; A. H. Mahnken (The Scientific World Journal)
Purpose. To investigate the safety and feasibility of the use of a vascular closure device (VCD) after endovascular procedures in swine. Material and Methods. In a study on endovascular therapy, VCD (StarClose, Abbott Vascular, Il, USA) was used in 20 female swines to achieve immediate hemostasis after percutaneous right femoral artery (FA) access. 10 animals were sacrificed immediately after the study and 10 animals were sacrificed 28 days after the initial study. To ensure complete hemostasis and patency of the femoral artery, a CT-angiography of the puncture site was performed on day 1 (acute and chronic group) and day 28 (chronic group). After the sacrifice, the femoral artery was explanted and examined macroscopically for signs of VCD dysfunction. Results. Technical success rate was 100% with immediate hemostasis being achieved in all animals. No animals showed evidence of hematoma. During explantation, only small traces of coagulated blood were found in the acute group, while there were no signs of hematoma in the chronic group. CT-angiography immediately after VCD application as well as before sacrifice (chronic group) showed patency of the FA in all cases. Conclusion. The use of VCD to achieve hemostasis after endovascular studies in swine is feasible and safe.